Artist Friends – Artist Foes: Egon Schiele and Oskar Kokoschka - Bonnefoit, Régine (My University, 2024)
The starting point for the chapter on artist friends and foes are two works created around 1917/18 in which Egon Schiele (1890–1918) and Oskar Kokoschka (1886–1980) each depict their friends and peers of that time gathered around a table. “Friends”, as Kokoschka’s painting is called, shows a private party with all chairs occupied, whereas Schiele leaves one or two chairs vacant in the various versions of his work. Both artists take a place of honor at the head of the table in the gatherings composed by them. Schiele used the oil painting “The Friends (Round Table)” as the motif for his poster for the 49th Exhibition of the Vienna Secession, which was held from 1st March to 1st April 1918. Schiele curated this group exhibition and also invited Kokoschka to participate, but the latter declined. This essay attempts to trace any personal contact between the two artists. In the light of scarce historical sources, this choice of topic may seem surprising. What is more, Kokoschka vehemently insisted in the 1940s that he had never met Schiele in person. He repeatedly denied any assumptions that he and Schiele had been friends. Taking into consideration the many patrons, collectors, clients and friends they had in common or the exhibition venues and galleries at which the two artists might have run into each other, it seems more than unlikely that they never met. Carl von Reininghaus, Oskar Reichel and Franz Hauer collected works by both Kokoschka and Schiele; both artists participated in the Internationale Kunstschau Wien 1909, in the exhibition Neukunst Wien at the Budapest Művészház in 1912, in the 1912 Sonderbund Exhibition in Cologne, in the Wiener Kunstschau held at the Berlin Secession in 1916 and other events. They had mutual friends, such as the painter Felix Albrecht Harta. Both corresponded with Arnold Schönberg during the same period of time, both executed postcards for the Wiener Werkstätte and drafts for Stoclet Palace in Brussels. Both were presumably equally disappointed by Stoclet’s rejection of their designs.
Künstlerfreundschaft – Künstlerfeindschaft: – Das Verhältnis zwischen Egon Schiele und Oskar Kokoschka
The essay is based on a lecture given by the author on November 9, 2023 on the occasion of the 5th Egon Schiele Symposium at the Leopold Museum: https://www.leopoldmuseum.org/egon-schiele-symposium/de
Keywords: Egon Schiele; Oskar Kokoschka